A case of advanced hepatocellular carcinoma wherein readministration was made possible due to successful transcatheter arterial embolization for intratumoral hemorrhage during Lenvatinib administration - Hara, Hidenobu; Nakano, Yu; Arai, Katsuhiro; Kaneko, Yuka; Sakaki, Kazuomi; Fukami, Yuichi; Ikemiyagi, Hidekazu; Yoshino, Kouhei; Sakita, Shinya (Nippon Shōkakibyō Gakkai zasshi, 2022)
The subject was a man in his late 70s who was seeing a family physician for diabetes and dyslipidemia on an outpatient basis. A routine medical checkup revealed liver dysfunction, prompting an abdominal ultrasound. As a result, a large hepatic tumor was discovered, prompting a thorough examination. The patient was diagnosed with hepatocellular carcinoma and multiple liver metastases, as well as tumor shadows that could indicate pulmonary metastases, after a thorough examination at our hospital. Due to the patient not having viral hepatitis or any drinking history and had formerly been confirmed as having fatty liver, a diagnosis of cirrhosis and hepatocellular carcinoma caused by NASH (nonalcoholic steatohepatitis) was given. A Child-Pugh score of 5 (A) and modified albumin-bilirubin (mALBI) grade 2 were used to maintain liver function. As a result, a 12-mg/day Lenvatinib treatment regimen was initiated. From the 6th day of the start of oral administration, the patient developed right hypochondralgia and loss of appetite. Blood samples showed increased levels of liver enzymes and inflammatory reaction, requiring hospitalization for closer examination. Intratumoral hemorrhage from hepatocellular carcinoma was discovered by dynamic CT scans. The patient's general condition was stable, and an angiogram was performed on the 3rd day of admission. As a result, persistent extravasation was discovered, necessitating transcatheter arterial embolization (TAE) treatment of the lesion for tumor vessel embolization. Thereafter, transient deterioration of the liver function occurred but an immediate improvement was seen. The patient was discharged without a recurrence of hemorrhage. An outpatient follow-up was performed, with blood test results indicating that liver function was maintained with a Child-Pugh score of 6 (A), and a dynamic CT showing that intratumoral hemorrhage was under control, allowing for readministration. Readministration of Lenvatinib was started at 4mg/day, one level lower, because the patient's body weight had dropped below 60kg. There are few reports on Lenvatinib-induced intratumoral hemorrhage, and this is a unique case worthy of reporting, with previous literary references, in which the entire process from intratumoral hemorrhage to readministration of Lenvatinib after embolization treatment has been documented.